A new method for current–voltage curve prediction in photovoltaic modules. Issue 6 (23rd February 2021) - Peña, Rafael; Diez‐Pascual, Ana M.; Díaz, Pilar García; Davoise, Lara Velasco
Abstract: In this work, a new method for obtaining the current–voltage curve for crystalline silicon and thin‐film flat panels is presented. It is based on the single‐diode model, with a variable shunt resistance and series resistance. New expressions for the shunt resistance and open circuit voltage as a function of the temperature and irradiance are deduced. Besides, a procedure to translate the series resistance to arbitrary conditions is proposed. The diode ideality factor and shunt resistance are obtained by optimization. The rest of the parameters that appear in the current–voltage curve are obtained from the module measurements by means of theoretical expressions. The procedure for obtaining the current–voltage curve under arbitrary operating conditions is also described. The results obtained with the developed model are compared with experimental measurements in cadmium telluride and amorphous silicon modules, and with results published in the literature for other technologies. The model faithfully reproduces the experimental values. For all the modules, the root mean square error for the maximum power is lower than 2% (below 1.5% in most cases). These errors are lower than those reported in the literature for other models. In particular, the results are significantly more exact in the case of thin‐film modules.